1999
DOI: 10.1038/sj.ijo.0801032
|View full text |Cite
|
Sign up to set email alerts
|

Serum glucagon concentration and hyperinsulinaemia influence renal haemodynamics and urinary protein loss in normotensive patients with central obesity

Abstract: OBJECTIVES: Insulin-resistance syndrome and hyperinsulinaemia are linked with cardiovascular disease (CVD) in the obese population. In particular, cardiovascular risk is more frequent in central obesity and is associated with microalbuminuria (MA). MA and changes of glomerular permeability to proteins in obesity might be related with renal haemodynamic modi®cations (that is glomerular hyper®ltration). Since glucagon is physiologically involved in renal haemodynamic regulation, the purpose of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
(25 reference statements)
0
12
0
1
Order By: Relevance
“…This was based on earlier reports demonstrating L-arginine to be effective against renal toxic or ischemic injury (33)(34)(35)(36)(37)(38)(39). L-Arginine supplementation significantly improved BUN (p < 0.01)) and serum creatinine (p < 0.05) clearance, as shown in Figure 5A and B, respectively.…”
Section: Plasma Pharmacokineticsmentioning
confidence: 61%
“…This was based on earlier reports demonstrating L-arginine to be effective against renal toxic or ischemic injury (33)(34)(35)(36)(37)(38)(39). L-Arginine supplementation significantly improved BUN (p < 0.01)) and serum creatinine (p < 0.05) clearance, as shown in Figure 5A and B, respectively.…”
Section: Plasma Pharmacokineticsmentioning
confidence: 61%
“…Plasma glucagon levels are abnormally elevated in both T1D and T2D subjects, indicating that a-cell hypersecretion is a common diabetic feature [196][197][198][199]. Abnormally high fasting glucagon levels, suggestive of a-cell hypersecretion, have been found also in normoglycemic insulin-resistant obese adults and adolescents [200][201][202][203][204]. In the latter group, high fasting glucagon levels were observed in the face of elevated fasting insulin levels, suggesting that a-cells manifested insulin resistance to the suppressive effect of insulin on glucagon secretion.…”
Section: Pancreatic A-cells Dysfunction May Contribute To Hyperglutammentioning
confidence: 99%
“…Moreover, evidence strongly suggests that microalbuminuria is also an independent predictor of cardiovascular disease in these. 54,55 Troglitazone and rosiglitazone have been shown to protect against nephropathy in animals. 12,56 Imano et al in a short 12-week study demonstrated that troglitazone, but not metformin decreased microalbuminuria in patients with incipient diabetic nephropathy without lowering blood pressure.…”
Section: Albuminuriamentioning
confidence: 99%